Professional divers: analysis of critical issues and proposal of a health protocol for work fitness - Pedata, Paola; Corvino, Anna Rita; Napolitano, Raffaele Carmine; Garzillo, Elpidio Maria; Furfaro, Ciro; Lamberti, Monica (La Medicina del Lavoro, 2016)
Introduction: From many years now, thanks to the development of modern diving techniques, there has been a rapid spread of diving activities everywhere. In fact, divers are ever more numerous both among the Armed Forces and civilians who dive for work, like fishing, biological research and archeology. AIM: The aim of the study was to propose a health protocol for work fitness of professional divers keeping in mind the peculiar work activity, existing Italian legislation that is almost out of date and the technical and scientific evolution in this occupational field. Method: We performed an analysis of the most frequently occurring diseases among professional divers and of the clinical investigation and imaging techniques used for work fitness assessment of professional divers. Results: From analysis of the health protocol recommended by D.M. 13 January 1979 (Ministerial Decree), that is most used by occupational health physician, several critical issues emerged. Very often the clinical investigation and imaging techniques still used are almost obsolete, ignoring the execution of simple and inexpensive investigations that are more useful for work fitness assessment. Conclusions: Considering the out-dated legislation concerning diving disciplines, it is necessary to draw up a common health protocol that takes into account clinical and scientific knowledge and skills acquired in this area. This protocol’s aim is to propose a useful tool for occupational health physicians who work in this sector.